2017
DOI: 10.15453/2168-6408.1339
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Students in Norway: Do Their Approaches to Studying Vary by Year In the Program?

Abstract: Approaches to studying may be influenced by students' age, maturity, and experience in higher education. Students' approaches to studying may develop toward deep and/or strategic approaches and away from a surface approach as they move through the curriculum, which is generally considered a positive development. This study aimed to identify differences in approaches to studying among first-, second-, and third-year students enrolled in an occupational therapy program. Three cohorts of students (n = 160) from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We also assessed how much of the total GPA variance was explained with the blocks of independent variables, and the analyses were performed for the total sample and for each of the countries separately. As previous studies have noted very few differences between students in different year cohorts (Bonsaksen, Thørrisen, & Sadeghi, 2017), year cohort was not included as an independent variable for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed how much of the total GPA variance was explained with the blocks of independent variables, and the analyses were performed for the total sample and for each of the countries separately. As previous studies have noted very few differences between students in different year cohorts (Bonsaksen, Thørrisen, & Sadeghi, 2017), year cohort was not included as an independent variable for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A notable exception is a study among Norwegian occupational therapy students [37] that revealed that students without prior higher education were more prone to adopt a surface approach to studying. However, studies exploring temporal changes in preferred approaches to study throughout the course of an education program have yielded inconclusive results [16,[31][32][33][34]. For instance, Bonsaksen et al [32] demonstrated a decrease in surface approach between first and third-year occupational therapy students, while Shah et al [34] reported a gradual shift from deeper to more surface learning among health sciences students.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies exploring temporal changes in preferred approaches to study throughout the course of an education program have yielded inconclusive results [16,[31][32][33][34]. For instance, Bonsaksen et al [32] demonstrated a decrease in surface approach between first and third-year occupational therapy students, while Shah et al [34] reported a gradual shift from deeper to more surface learning among health sciences students. Our results question the importance of maturity in understanding students' approaches to study, although it should be noted that the age distributions in our samples were quite narrow, with the majority of students being aged between 20 and 24 years (national sample: 71.7 %; international sample: 57.6 %).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data collection procedure, which included three subsequent measurement occasions, moved the field of study beyond those of previous studies merely comparing cohorts of students [39,40] and allowed for the assessing the stability of group differences across time. However, the study did not address individual changes in perceptions of the learning environment across time.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%